(untitled) (Acta Scientiarum. Agronomy, 2019)
Since 2001, the disease known as ’guava decline’, resulting from the interaction between the phytonematode Meloidogyne enterolobii and the fungus Fusarium solanie, has caused direct and indirect economic losses to the entire guava production chain. Given the lack of sources of resistance in guava genotypes, interspecific hybrids of Psidium spp. were obtained for resistance to the nematode M. enterolobii. To classify the level of resistance of the interspecific hybrids, we evaluated the plant classification methodologies proposed by Oostenbrink (1966) and Moura and Régis (1987). Estimates of genetic parameters were obtained using the REML/BLUP approach. Interspecific hybrids resistant to M. enterolobii were selected that can be used as rootstocks or in new crosses for the development of the guava breeding program.